The "Microscopic Algae in the hard coral communities" - Velasquez, Gregorio T. (1979)
Four better known classes of the microscopic algae are represented in the study, namely: Myxophyceae, Rhodophyceae, Chlorophyceae, and Phaeophyceae, in that order of abundance and number of species (See Table 1). Representative samples of hard corals and edible fishes frequenting and or living in the coral communities are collected and with the algae were studied and represented in photographs. (Figures la and b).The discussion centers on the significant role of the algae with which the other minute organisms in the corals were included and analyzed to explain the transfer of energy in the trophic level of food forms involved through the physio-biochemical processes. Such is a special activity in a complex recycling. A brief presentation of some selected background work with relevance to the research is reviewed. Goggles easy to use in diving and improvised bows and arrows suited together to catch the fishes in the corals are suggested for distribution freely. It should introduce a practical and least expensive rural technology in far-away places generally much neglected.